Impact properties of acrylate rubber-modified PVC: Influence of temperature - Azman, Hassan; Haworth, Barry (Elsevier BV, 2006)
The enhancement of the impact resistance of plastics through the introduction of a rubbery dispersed phase is one of the means to develop high impact strength polymers and has been exploited commercially on a large scale. Rubber-toughened PVC-U or high impact PVC-U is one such important class of rubber-toughened plastics material which has been developed and has a wide application in the building and furniture industries. The type of impact modifiers most commonly used for window frame applications are chlorinated polyethylene, ethylene-vinyl acetate and acrylate modifiers. The current trend shows the importance and popularity of high impact-acrylate-modified PVC. The objective of this research is to extend the existing understanding of toughness enhancement in rubber-toughened polymer materials to acrylate rubber-modified PVC. This paper reports on the effect of temperature on the impact strength of acrylate rubber-modified PVC-U using the instrumented falling weight impact test (IFWI) method. Toughening and fracture mechanism in acrylate-modified PVC were also investigated. The results show that all the acrylate rubber-toughened PVC blends have successfully shifted the ductile–brittle transition points to a lower temperature. However, the impact modifiers were found to differ in their efficiency to shift the ductile to brittle transition. The findings from the SEM study shows that the fibrous yielding phenomenon observed is an indication of the transition of the brittle stage to ductile stage and correlates well with the large increases of the impact strength.